PENGEMBANGAN BAHAN AJAR ENGLISH FUN LEARNING DENGAN APLIKASI CANVA MATERI HOW DO YOU GO TO SCHOOL KELAS IV MADRASAH IBTIDAIYAH - Suttrisno; Nasikah, Imroatun; Habibullah, M. Romadlon (STAI Ma'had Aly Al-Hikam Malang, 2024)
The development of English Fun Learning teaching materials presents a creative approach to English language learning, incorporating engaging elements such as games, songs, instructional content, quizzes, and practice questions. This research aims to explore the development of teaching materials for English language instruction at MI Darul Falah Menilo in class IV, specifically focusing on the validation of the appropriateness of these materials concerning the topic